Criminalization of the IVF Disposal Procedure for Surplus Embryos a Comparative Study: A Comparative Study - Alqaydi, Shaikha; Sayed, Mohamed (Journal of Legal Sciences, 2026)
This study aims to shed light on the criminal classification of the procedure for disposing of surplus embryos resulting from in vitro fertilization (IVF), in accordance with various legal frameworks, with a particular focus on UAE Law No. 17 of 2023 on Medical Assistance in Reproduction. The study examines two types of surplus embryos: those inside the uterus, which are selectively reduced through abortion, and those outside the uterus, which are left without medical care until they deteriorate. The study employs a descriptive-analytical approach to examine the legal texts, alongside a comparative approach to explore the perspectives of Islamic law and different legal systems. The findings indicate that the UAE legislator has not explicitly defined the legal framework for embryo reduction inside the uterus, despite its practical application, leaving a legislative gap that may impact the protection of both embryos and mothers.